(untitled) (Acta Scientiarum. Biological Sciences, 2015)
This work aimed to evaluate the relationship between parameters of fish communities and the habitat structure of a stream. Twenty three stretches six meters long were evaluated in the Samambaia stream located inside the Sumidouro Park, Rio das Velhas basin, state of Minas Gerais, Brazil. Fish samplings and habitat characterization were made for each stretch. Seven variables of habitat (vegetal cover, width, depth, substrate, flow, presence of aquatic plants and leaf litter) and two variables characterizing the longitudinal gradient (altitude and distance from the Sumidouro lagoon) were assessed. The fish community responded to habitat changes, presenting variation in richness and composition of species. Richness was positively influenced by the presence of leaf litter and aquatic plants. Furthermore, through similarity data (NMDS) and habitat structure (PCA), it was possible to observe the separation of the 23 stretches into two groups with a dissimilarity of approximately 90%. We concluded that the variation in richness and composition of species throughout the stream was strongly related to the variables of habitat structure. This variation is clearer when considering the longitudinal gradient which highlights a great difference between stretches nearer and farther from the mouth of Samambaia stream.